The interplay between learner beliefs and foreign language anxiety: insights from the Turkish EFL context. Issue 2 (4th March 2021) - Aslan, Erhan; Thompson, Amy S.
ABSTRACT: Foreign language learning in classroom settings has long been found to be associated with anxiety. Though it is known that sources of foreign language anxiety are varied, whether anxiety is related to learners' inherent beliefs about language learning is understudied. To this end, the present study examines the possible relationship between learner beliefs and language anxiety in the under-researched Turkish EFL context. A population of university-level Turkish EFL learners ( n = 153) completed the Beliefs about Language Learning Inventory (BALLI) and the Foreign Language Classroom Anxiety scale (FLCAS). The underlying constructs in both instruments were explored using an Exploratory Factor Analysis (EFA). A series of Pearson Product-Moment Correlation Coefficient (PPMCC) tests were performed on the factor scores from both instruments. The findings revealed that fear of ambiguity was positively linked to classroom performance anxiety and negative feelings towards English. In addition, the more confident learners feel themselves using English, the more desire they seem to have to interact with native speakers. Overall, positive beliefs about language learning may be helpful in reducing anxiety and boosting confidence in language learning. These findings not only enhance our understanding of the complex psychology of language learning but also have important implications for instructed EFL/ESL settings.